The Effects of a Home-Based Intervention for Young Children with Developmental Delays in Vietnam: 6-Month Follow-Up Results - Shin, Jin Y; Duc, Son Nguyen; Accardo, Michael; Dill, Charles A (Archives of Community Medicine and Public Health, 2018)
We assessed the long-term efficacy of a home-based intervention program for young children (n = 46, ages ranging from 3 to 6 years) with developmental delays in Vietnam. The current paper reports on the six-month follow-up evaluation of the children after their six-month intervention ended. At the same time, the children who were in a wait-list control group during the initial intervention program obtained the same intervention for these six months and their outcomes are reported in this paper. It was hypothesized that after completing the intervention program, the children would retain their adaptive functioning during the six-month follow-up period. It was also expected that the children who had previously served as controls would see similar gains after they received the intervention to those seen in our initial intervention group. The intervention follow-up group (n= 21) was assessed at 6 (the end of their intervention), 9 and 12 months, following their initial assessment at 0 and 3 months during the intervention. The children who received the delayed intervention (n = 25) were assessed at 6, 9 and 12 months during the intervention, following their initial assessment at 0 and 3 months as controls. The Vineland Adaptive Behavior Scale – II (VABS-II) was administered to identify the children as developmentally delayed and to assess the outcomes throughout the intervention and follow-up periods. The initial intervention group showed maintenance of adaptive behaviors in the areas of socialization and communication skills. The delayed intervention group showed improved socialization and communication skills after receiving the intervention. While validating the positive outcomes from the initial intervention program, the study showed that those skills could be maintained at least for six months, probably due to the ability of the caregivers to continue to apply their skills in training and educating their children and/or their increased ability to identify and use resources in the schools and communities. The results are promising in that the children showed improvement in a relatively short period of time by working with college students with limited teaching experience and were able to maintain the gains acquired during the intervention program.